2015
DOI: 10.1111/sms.12405
|View full text |Cite
|
Sign up to set email alerts
|

Results of voluntary cardiovascular examination of elite athletes in Denmark: Proposal for Nordic collaboration

Abstract: We investigated the cardiovascular status of elite athletes in Denmark, the extent of abnormal cardiac findings--both training related and pathologic--and how participating in cardiac examination was perceived by the athletes. A standardized protocol of questionnaires, physical examination, resting electrocardiogram, and 2D echocardiography was used. In total 1347 elite athletes were invited; 516 athletes (38%) from 30 different sports participated. Results were stored in a web-based database for future resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…12,13 Several prospective, observational studies have compared the results of a medical history and physical examination. [13][14][15] A meta-analysis of 15 studies reported a pooled sensitivity of 20% for history and 9% for physical examination in identifying disease 13 and subsequent studies have reported similar results. [14][15][16] However, these studies did not have a "gold standard" comparator, because denominators were created from total positive screening results.…”
Section: Elements Of CV Screeningmentioning
confidence: 87%
See 3 more Smart Citations
“…12,13 Several prospective, observational studies have compared the results of a medical history and physical examination. [13][14][15] A meta-analysis of 15 studies reported a pooled sensitivity of 20% for history and 9% for physical examination in identifying disease 13 and subsequent studies have reported similar results. [14][15][16] However, these studies did not have a "gold standard" comparator, because denominators were created from total positive screening results.…”
Section: Elements Of CV Screeningmentioning
confidence: 87%
“…[13][14][15] A meta-analysis of 15 studies reported a pooled sensitivity of 20% for history and 9% for physical examination in identifying disease 13 and subsequent studies have reported similar results. [14][15][16] However, these studies did not have a "gold standard" comparator, because denominators were created from total positive screening results. 13 Therefore, false-negative rates and negative predictive values cannot be accurately assessed, supporting the view that such approaches should be considered poor for identifying disease but might assist in identifying athletes at risk of a CV event.…”
Section: Elements Of CV Screeningmentioning
confidence: 87%
See 2 more Smart Citations
“…The primarily Caucasian athletes participated in a study of voluntary cardiac pre-participation screening [26]…”
Section: Athletesmentioning
confidence: 99%